Multiple DG Placements in Distribution System for Power Loss Reduction Using PSO Algorithm. (2016) - Prakash, D.B.; Lakshminarayana, C.
Abstract: Optimal placement and optimal sizing of Distributed Generation (DG) for the sake of reduction in power loss and improvement of voltage profile in distribution networks are investigated in this paper. Particle Swarm Optimization (PSO) algorithm is used to find out the best location and optimal size of DG. Complete analysis is carried out on IEEE 33-bus and IEEE 69-bus radial distribution systems. Each system is considered for two different cases and comparative results obtained will demonstrate the effectiveness of the proposed method as far as placement, sizing of DG and minimization of power losses are concerned.